Attention or Distraction? The Impact of Mobile Phone on Users' Psychological Well-Being - Chu, Jianxun; Qaisar, Sara; Shah, Zakir; Jalil, Afsheen (Frontiers in Psychology, 2021)
Cumulative evidence has demonstrated that mobile phone distraction, in particular among emerging adults, is a growing problem. Considerable efforts have been made to contribute to the literature by proposing the cognitive emotion preoccupation which acts as an underline mechanism through which mobile phone distraction results in reducing psychological well-being. The proposed model gets its support from distraction-conflict theory which reveals that users, with high attention control, are better to cope up with the negative consequences of mobile phone distraction. The data, consists of 914 university students in China, was analyzed through statistical tools. The results support that mobile phone distraction has a significant positive relationship with cognitive emotional preoccupation which negatively affects users’ psychological well-being. Our findings also reveal that attention control moderated the mediation effect of cognitive emotional preoccupation in association between mobile phone distraction and psychological well-being. The theoretical and practical implications are also discussed along with limitation and future research.